2020
DOI: 10.1136/thoraxjnl-2019-213547
|View full text |Cite
|
Sign up to set email alerts
|

Comparing treatment effects of a convenient vibratory positional device to CPAP in positional OSA: a crossover randomised controlled trial

Abstract: ObjectivesUp to 77% of patients with obstructive sleep apnoea (OSA) have positional OSA (POSA) but traditional positional therapy (PT) methods have failed as they were poorly tolerated. New convenient vibratory PT devices have been invented but while recent studies suggest high treatment efficacy and adherence, there are no published data comparing these devices directly with continuous positive airway pressure (CPAP). Our objective is to evaluate if a convenient vibratory PT device is non-inferior to CPAP in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Similarly, MMO can be an alternative for patients experiencing CPAP failure [106]. Finally, despite very low certainty of evidence, patients with mild to moderate position-dependent OSA can be treated with vibratory positional therapy as compared to CPAP or as compared to mandibular advancement [83,84,88,89].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, MMO can be an alternative for patients experiencing CPAP failure [106]. Finally, despite very low certainty of evidence, patients with mild to moderate position-dependent OSA can be treated with vibratory positional therapy as compared to CPAP or as compared to mandibular advancement [83,84,88,89].…”
Section: Discussionmentioning
confidence: 99%
“…For PICOs 7 and 8, 1632 studies were originally identified, five of them for PICO 7, including 221 participants who were randomised to either positional therapy or CPAP (supplementary figures e7 and e12, supplementary tables e10 and e18) [78][79][80][81][82][83][84]. For the definition of positional OSA, all studies shared the criterion of the supine AHI to be at least twice as high as the nonsupine AHI.…”
Section: Summary Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…A prevalence of 13% of pOSA is close to figures of the literature. Considering that pOSA can be treated effectively with specific instruments (15), such as postural trainers or mandibular advancement devices, when waiting lists for standard diagnosis cause a significant delay in the management, the treatment could be instituted immediately. The percentage of time spent in the different positions is reported under each RIC, and if less than 10% of time is spent in the supine position, the reliability is low and requires further validation.…”
Section: Discussionmentioning
confidence: 99%